Impact of preoperative frailty on regaining walking ability in patients after cardiac surgery: Multicenter cohort study in Japan. (July 2019) - Yuguchi, Satoshi; Saitoh, Masakazu; Oura, Keisuke; Tahara, Masayuki; Kamisaka, Kenta; Kawamura, Tomonori; Kato, Michitaka; Morisawa, Tomoyuki; Takahashi, Tetsuya
Highlights: Preoperative SPPB score is a factor of the postoperative day of the reacquisition of walking ability after cardiac surgery. Frailty that the SPPB score is ≦9 prolongs the day of reacquisition of walking ability. The SPPB score is a factor which affects the rate of reacquisition of walking ability postoperatively. The preoperative SPPB cutoff value which indicates the feasibility of reacquisition of walking ability postoperatively is ≧9. Abstract: Background: This study aimed to examine the relationship between preoperative frailty and the reacquisition of walking ability in patients after cardiac surgery. Methods: 450 patients who underwent cardiac surgery were included as subjects. We implemented the Short Physical Performance Battery (SPPB) before surgery and classified subjects into three groups according to the SPPB score: SPPB 10–12, SPPB 7–9, and SPPB 0–6. We examined the postoperative day and the rate of the reacquisition of walking ability after surgery, and compared them among three groups. In addition, we calculated the cutoff value for the SPPB score to regain walking ability by performing a receiver operating characteristic curve analysis. Results: The postoperative day of the reacquisition of walking ability in SPPB 10–12 was earlier than other groups (SPPB 10–12: 4.0 days, SPPB 7–9: 4.5 days, SPPB 0–6: 6.0 days, p < 0.01), and SPPB 0–6 was lower than other groups in the rate of the reacquisition of walking ability (SPPB 10–12: 98.8%, SPPB 7–9: 96.4%, SPPB 0–6: 76.2%, p < 0.01). The cutoff value for SPPB was ≧9(Area under the curve: 0.85, sensitivity: 0.82, specificity: 0.71, p < 0.001). Conclusion: Preoperative frailty affected the day of the reacquisition of walking ability in patients after cardiac surgery. The preoperative SPPB cutoff value which indicates the feasibility of reacquisition walking ability after surgery was ≧ 9.